The Effect of Using E-WoHealth on Knowledge, Attitudes and Behaviors About Body Image and Anemia in Young Women - Fadlun Ishak; Yusring Sanusi Baso; Mardiana Ahmad; Andi Nilawati Usman; Deviana Soraya Riu; Muhammad Tamar (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The prevalence of anemia in adolescents in Indonesia has increased by 32%, meaning that 3-4 out of 10 adolescents suffer from anemia in the age group 15-24 years is the largest proportion who experience anemia. This research uses the Combined Method (Research and Development), and the research design uses pre-experimental. The research design develops and validates learning media, namely E-WoHealth, in several stages: analysis of learning media needs, learning media development, design, expert test validation, TAM test, and tininal product of media. The development stage starts with an analysis of the needs of students at Junior High School, Six Gorontalo City. The findings show that the pre-test and post-test values for knowledge, attitudes, and behavior of young women have increased significantly, with a p-value of 0.000 <0.05, meaning that there are differences in the knowledge, attitudes, and behavior of young women before and after being educated using E-WoHealth. In conclusion, web-based E-WoHealth has an effect on the knowledge, attitudes, and behavior of young women regarding body image and anemia. Video and e-modules can be used as alternative educational media to prevent health problems in adolescents, especially anemia. They can improve the habits or behavior of adolescents by assessing themselves by comparing themselves with others to create self-confidence or body image. Positive for teenagers. It is hoped that schools can apply various methods, one of which is the use of animated videos and e-modules that can be accessed using smartphones.